Retreat of the Greenland Ice Sheet leads to divergent patterns of reconfiguration at its freshwater and tidewater margins - Jonathan Ryan; Theo Ross; Sarah Cooley; Dominik Fahrner; Nicole Abib; Victoria Benson; David Sutherland (Journal of Glaciology)
Greenland's marine- and land-terminating glaciers are retreating inland due to climate warming, reconfiguring the way the ice sheet interacts with its proglacial environment. Here we use three decades of satellite imagery to determine whether the ice-sheet margin is becoming more or less exposed to marine and lacustrine processes. During our 1990–2019 study period, we find that the length of ice-sheet perimeter in contact with the ocean shrank by 12.3 ± 3.8% (196.2 ± 10.4 km), due to the retreat of marine-terminating glaciers into narrower fjords. On the other hand, we find that the length of the ice-sheet perimeter in contact with freshwater lakes exhibited more divergent trends that is better explored at regional scales. The length of ice–lake boundaries increased in southwest, north and northwest Greenland but declined in southeast and central east Greenland. The magnitude of change we document during our study period leads us to conclude that the ice sheet is poised for further, substantial reconfiguration in the coming decades with consequences for the flux of fresh water, nutrients and primary productivity in Greenland's terrestrial and oceanic environment.